An innovation systems approach to capacity development: Insights from learning exercises with the Feed the Future Fish Innovation Lab in Nigeria - Ye, Jia Yi; Brouwers, Jan; De Roo, Nina (International Food Policy Research Institute, 2019)
This report details the project’s engagement with WorldFish Nigeria, Mississipi State University, Washington University in St. Louis, and its “Quick Start” Fish Innovation Lab (FIL) in Nigeria. The engagement—which we frame as a case study in systems-oriented capacity development—was conducted in 2019, and included a series of multistakeholder learning events held in Ibadan, Nigeria, during early September 2019.